Severe dengue with fulminant myocarditis and acute coronary syndrome in a young woman:case report. - Belmontes-Gutiérrez , D.A; Isais-Moreno , D.M.; Castro-Ruales , J.M.; Hernández-Aguirre , U.G.; Moreno Velasco , P.A. (Revista de Ciencias Médicas Torreón, 2026)
Dengue is an endemic viral disease that is usually self-limitedbutmayprogresstosevereorgandysfunction.Cardiovascular involvement is uncommon and can present asmyocarditis, arrhythmias, or a clinical picture mimickingacute coronary syndrome. We report a 34-year-old womanwith hypertension and class II obesity with confirmed denguewho developed intense abdominal pain, metabolic acidosis,elevated troponin I and CK-MB, and ST-segment elevationin leads V2–V4. Point-of-care echocardiography showedapical hypokinesia and systemic venous congestion, raisingthe differential diagnosis of fulminant myocarditis versusacute myocardial infarction. Given the high bleeding riskinherent to severe dengue, initial antiplatelet therapy waswithheld. Despite early transfer to a tertiary center, the patientdeteriorated rapidly, developing cardiogenic shock andcardiac arrest with fatal outcome. This case highlights thediagnostic and therapeutic challenges of dengue-relatedmyocardial injury and underscores the need for earlyrecognition and individualized management.
Keywords: Dengue; fulminant myocarditis; acute coronary; syndrome; cardiogenic shock.